Analisis Optimalisasi Distribusi Logistik untuk Meningkatkan Efisiensi dan Keefektifan Operasional pada PT. XX - Cahyani, Amalia Dwi; Aisha, Najwa Shanaya; Rachmadhani, Andi Intan; Vincent, Vincent; Rahmadhani, Gina; Ulfani, Dulia; Tsani, Rubby Rahman; Handayani, Melia (Fakultas Teknik Universitas Tulang Bawang, 2024)
In an era of globalization and tight competition, efficiency and operational efficiency are crucial to the success of companies, especially in supply chain management. Logistical distribution is a key element that ensures smooth flow of goods to the end consumer. PT.XX is a company in the fields of construction, logistics, and storage tanks, facing various operational challenges. The challenges include the company's transportation constraints, delays in the delivery of raw materials from vendors, as well as inadequate production facilities for heavy goods. To address these challenges, PT.XX needs to implement comprehensive and responsive logistical distribution strategies needed to improve the efficiency and efficiency of distribution, which supports the sustainable growth of the company. The study uses descriptive approaches and analysis of fishbone diagrams to provide a clear picture of the problems faced by PT. XX and measurable practical solutions. The results of this research are expected to improve the transportation system, the quality of the delivery of raw materials, and prepare an adequate production area for large-scale goods, so that operations run smoothly. Keywords: Distribution Logistics, Operational Efficiency And Effectiveness, Operational.